Nursing Assistant Perceptions of Their Role in Quality Improvement Processes in Nursing Homes. Issue 3 (July 2016) - Davila, Heather; Abrahamson, Kathleen; Mueller, Christine; Inui, Thomas S.; Black, Aaron G.; Arling, Greg
Abstract : Nursing assistants provide the majority of direct resident care in nursing homes and are centrally involved in implementing quality improvement (QI), yet little is known about their experiences in QI. Interviews with nursing assistants found that respondents perceive themselves as having a unique and important role in QI. They described key outcomes of QI as positive gains in the daily lives of residents, improved work processes, and increased time between staff and residents. Abstract : Supplemental Digital Content is Available in the Text.